12 What Do Things Want? Object Design as a Middle Range Theory of Material Culture. Issue 1 (September 2015) - Robb, John; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT Material culture theorists in archaeology often argue directly from abstract philosophical models to the interpretation of specific examples which exemplify a particular paradigm well; there has been little attempt to develop methods which work across the entire range of material things we make and which relate the social projects they form part of to the actual material characteristics of things. This paper attempts to refocus attention upon objects by asking the design question: what social task are they intended to accomplish, and what characteristics (material and otherwise) enable them to do it? It develops a general model in which objects incorporate knowledge of the responses they are intended to provoke; this incorporated knowledge gives archaeologists analytical purchase for understanding ancient things. This thesis is illustrated both by a survey of some common strategies of material efficacy and by two capsule examples of how aesthetic style as a design feature provokes specific reactions on the part of people using objects, linking them into particular kinds of social relationships.